MODERASI BERAGAMA DAN UNIVERSALISME ISLAM: Kebijakan FKPT Jambi Berbasis Pemikiran Nurcholish Madjid - Kusnadi, Edy; Rafii, Muhammad; Hatta, Juparno; Mesalina T, Juliana (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2024)
Jambi, is not free from the threat of terrorism in managing diversity. It is recorded that cases related to the issue of radicalism have been found in the Jambi region. The Jambi Terrorism Prevention Coordination Forum (FKPT) has taken integral-participatory action in preventing the development of radicalism and terrorism in Jambi. The actions and policies of the Jambi FKPT seek to build tolerant and inclusive diversity in deradicalization and prevention of radicalism and terrorism. The purpose of this article focuses on the Jambi FKPT policy in narrating diverse moderation and analyzing these programs and policies from the perspective of Nurcholish Madjid. This article uses qualitative methods and literature studies. By conducting interviews with the Jambi FKPT subjects, and reading policies and programs. Furthermore, it is analyzed using a content approach, analysis, and discourse analysis. Moderation education is mainstreamed in carrying out deradicalism and preventing radicalism in Jambi. The discourse of moderation is in line with the universalist view of Islam from Nurcholish Madjid, in building the character of religious people with a tolerant and inclusive attitude. The concept is in Islamic universalism, while the practice is in religious moderation. In an effort to deal with terrorism, FKPT Jambi adopted Cak Nur's thinking as a basis for managing diversity in Jambi. The resolution in deradicalization in Jambi was developed by FKPT by building a stronger social foundation in maintaining harmony amidst the plurality of society. Its policy encourages religion not only as a ritual dimension, directing the development of basic understanding of religion into public ethics and spiritual vision as a resolution in managing diversity in Jambi.